Wood Properties of 5-year-old Fast Grown Teak - Ratih Damayanti; Barbara Ozarska; I Ketut N. Pandit; Fauzi Febrianto; Gustan Pari (Masyarakat Peneliti Kayu Indonesia, 2018)
Jati Unggul Nusantara (JUN) is one of fast growing plantation teak that has been widely cultivated in Indonesia. This teak has been developed to be harvested after 5 years when its diameter reaches 25-32 cm (diameter at breast high). The diameter of JUN is usually three times larger than the conventional plantation teak (teak cultivated from seed) at the same age, and the same as 30-40 year-old mature teak. Preliminary research was conducted to determine anatomical and selected physical properties of 5-year-old JUN teak, as well as its suitability for furniture production. The results revealed that wood color, texture, and grain pattern of JUN were slightly different from the mature conventional teak. The length of fiber cells was similar as in the mature teak. There were differences in ultramicroscopic structure of JUN: the mean micro fibril angle was narrower, and the crystallites degree was larger. Shrinkage values from green to 12% moisture content were: 0.70 (radial-R) and 1.62 (tangential-T), and from green to oven dry were 1.59 (R) and 3.29 (T). T/R ratio was 2.34. Specific gravity in air dry condition was 0.52. Based on the research results it appears that 5-year-old JUN may be suitable for the production of medium quality furniture products. More research is required to investigate and enhance the properties of JUN for high quality products.